Experiences of women participating in a human papillomavirus-based screen-triage-and treat strategy for cervical cancer prevention in Malawi - Lee, Fan; McGue, Shannon; Chapola, John; Dunda, Wezzie; Tang, Jennifer H.; Ndovie, Margret; Msowoya, Lizzie; Mwapasa, Victor; Smith, Jennifer S.; Chinula, Lameck (Frontiers in Oncology, 2024)
Objective: To explore the experiences of Malawian women who underwent a human papillomavirus (HPV)-based screen-triage-treat algorithm for cervical cancer (CxCa) prevention. This algorithm included Gene Xpert HPV testing of self-collected vaginal samples, visual inspection with acetic acid (VIA) and colposcopy for HPV-positive women, and thermal ablation of ablation-eligible women.In-depth interviews were conducted with participants of a trial that evaluated the feasibility of a HPV-based screen-triage-treat algorithm among women living with HIV and HIV negative women in Lilongwe, Malawi. Participants were recruited from 3 groups: 1) HPV-negative;2) HPV-positive/VIA-negative; 3) HPV-positive/VIA-positive and received thermal ablation.Interviews explored baseline knowledge of CxCa and screening, attitudes towards self-collection, and understanding of test results. Content analysis was conducted using NVIVO v12.Results: Thematic saturation was reached at 25 interviews. Advantages of HPV self-collection to participants were convenience of sampling, same-day HPV results and availability of same-day treatment. There was confusion surrounding HPV-positive/VIA-negative results, as some participants still felt treatment was needed. Counseling, and in particular anticipatory guidance, was key in helping participants understand complex screening procedures and results. Overall, participants expressed confidence in the HPV screen-triage-treat strategy.Discussion: HPV testing through self-collected samples is a promising tool to increase CxCa screening coverage. A multi-step screening algorithm utilizing HPV self-testing, VIA triage and thermal ablation treatment requires proper counseling and anticipatory guidance to improve patient understanding. Incorporating thorough counseling in CxCa screening programs can change women's perspectives about screening, build trust in healthcare systems, and influence healthcare seeking behavior towards routine screening and prevention.